Credit Restructuring Policy and Its Impact on Banking Financial Performance: Case Study at Bank in Papua - Hasan Basri Umar; Michael J. Kespo (International Journal of Applied Business and International Management, 2024)
The COVID-19 pandemic significantly disrupted global economies, including Indonesia's banking sector, compelling banks to implement credit restructuring policies to support struggling businesses. This study examines the impact of Bank Papua's credit restructuring policy on debtor businesses and the bank's financial performance across three periods: before, during, and after the COVID-19 pandemic. Key performance indicators analyzed include LDR, ROA, NIM, and NPL. This study uses a Paired Sample T-test for data analysis. The findings show that the credit restructuring policy during COVID-19 had no significant impact on Bank Papua's financial performance, as all hypotheses (H1–H4) were rejected. The LDR remained stable, indicating effective liquidity management despite economic challenges. ROA showed no significant changes, reflecting steady profitability despite business disruptions. NIM experienced minor fluctuations during the pandemic due to adjustments for restructured loans but stabilized post-pandemic. Although NPL levels increased due to debtors' financial struggles, they remained within acceptable regulatory limits, demonstrating effective credit risk management. Overall, the restructuring policy provided relief to debtors but had minimal impact on the bank's financial indicators, highlighting the importance of balancing debtor support with maintaining financial stability during economic crises.